The correlation of factors affecting the endometrial thickness with pregnancy outcome in the IUI cycles - Hadiss Kamyab; Sayed Noureddin Nematolahi Mahani; Victoria Habibzadeh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Many studies have been carried out to understand the effect of endometrial thickness on the reproductive outcome while the factors affecting the pattern itself are still unknown. Objective: To determine the factors such as age and the number of follicles that could affect the endometrial thickness Materials and Methods: This study was conducted as a retrospective study on 680 infertile women considered for intrauterine insemination (IUI). IUI protocol was sequential regimen of clomid and gonadotropin. Endometrial thickness measurement was done on the day of HCG administration. Correlation between endometrial thickness and factors such as age, total follicle numbers, dominant follicle numbers, gonadotropine ampule numbers and pregnancy rate were assessed. Results: The mean endometrial thickness was 7.2±1.8 mm. The endometrium was thinner in older patients compared with younger ones. But in all age ranges pregnancy rate was higher in endometrial thickness 6< ET≤10 mm (p<0.05).Conclusion: We did not find any correlation between age, number of follicles and gonadotropine ampoules with endometrial thickness but in all age ranges, there is a possibility of higher chance of pregnancy in endometrial thickness 6 < ET≤10 mm.